The Effect Of The Problem-Based Learning Model Using Documentary Film Medium On The Historical Literacy Abilities Of Grade XI Students Of SMA Negeri 8 Pandeglang: Pengaruh Model Preoblem Based Learning Dengan Media Film Dokumenter Terhadap Kemampuan Literasi Sejarah Siswa Kelas XI SMA Negeri 8 Pandeglang - Ananda Mutiara; Nashar; Yuni Maryuni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Historical literacy skills can be enhanced through the learning process, particularly in history education. However, in practice, there is a lack of effective learning media and facilities to support the development of students’ historical literacy skills. Therefore, this study aims to improve the historical literacy skills of Grade XI students at SMA Negeri 8 Pandeglang through the implementation of a Problem-Based Learning (PBL) model assisted by documentary film media. Specifically, this study seeks to determine whether the use of the Problem-Based Learning model with documentary film media has a significant effect on students’ historical literacy skills and whether it contributes to an improvement in those skills. This study employed a quasi-experimental method using a nonequivalent control group design. The research involved an experimental class and a control class. The sample consisted of students from Class XI IPS 1 as the control group and Class XI IPS 3 as the experimental group. The results of the statistical analysis, using an independent samples t-test, showed a significance value of 0.00 (< 0.05), indicating that H₀ was rejected and Hₐ was accepted. Furthermore, the improvement in students’ historical literacy skills was measured using the N-Gain test. The findings revealed that the experimental class achieved an average N-Gain score of 48.53, while the control class obtained an average N-Gain score of 35.23. Therefore, it can be concluded that the implementation of the Problem-Based Learning model supported by documentary film media has a significant positive effect on, and contributes to the improvement of, the historical literacy skills of Grade XI students at SMA Negeri 8 Pandeglang.